The Ultrasound-Guided Transversus Abdominis Plane Block for Anterior Iliac Crest Bone Graft Postoperative Pain Relief: A Prospective Descriptive Study. Issue 6 (1st October 2010) - Chiono, Julien; Bernard, Nathalie; Bringuier, Sophie; Biboulet, Philippe; Choquet, Olivier; Morau, Didier; Capdevila, Xavier
Abstract : Background: Acute postoperative pain and nerve injuries frequently lead to neuropathic chronic pain after anterior iliac crest (AIC) bone graft. This prospective study evaluated postoperative pain relief after preoperative ultrasound-guided transversus abdominis plane (TAP) block for orthopedic surgery with an AIC bone harvest and the prevalence of pain chronicization at 18 months after surgery. Methods: Thirty-three consecutive patients scheduled for major orthopedic surgery with an AIC harvest for autologous bone graft were studied. Preoperative TAP blocks were performed under in-plane needle ultrasound guidance, anterior to the midaxillary line (15 mL ropivacaine 0.33%). The extent of sensory blockade was evaluated at 20 mins with cold and light-touch tests. Pain at the iliac crest graft site was assessed at rest by visual analog scale (VAS) scores in the postanesthetic care unit, and at 1, 6, 12, 24, and 48 hrs after surgery. Time for first request of morphine and total morphine consumption were recorded. Eighteen months after surgery, each patient was interviewed by phone about the importance and localization of pain chronicization. Results: Median VAS score was 0 (range, 0-7) at all periods of assessment. At 20 mins, 62.5% of the patients reported complete anesthesia, and 34% hypoesthesia. The sensory blockade extent ranged from T9 (T7-T11) to L1 (T11-L2) in median (range) values. At 18 months, 80% of patients did not complain about pain or discomfort at the iliac crest site; 20% reported pain chronicization at the iliac crest site (VAS scores 2-4). Five patients (26%) complained about numbness at the iliac crest area. Conclusions: Ultrasound-guided TAP block is an appropriate technique for postoperative analgesia after AIC bone harvest in orthopedic surgery.